Ezetimibe: an update on its clinical usefulness in specific patient groups. (January 2017) - Hammersley, Daniel; Signy, Mark
The aim of pharmacological lipid modification is to reduce low-density lipoprotein cholesterol (LDL-C) as a means of either secondary or primary prevention of cardiovascular disease. Statins are the first-line therapy for pharmacological lipid modification. Ezetimibe is a drug which reduces LDL-C by selectively inhibiting intestinal cholesterol absorption. This provides an alternative pharmacological approach to that of statin therapy to reduce LDL-C. Ezetimibe has been shown to significantly reduce levels of LDL-C and recently, as demonstrated in the IMPROVE-IT trial, to reduce the rate of cardiovascular events in high-risk patients. Ezetimibe therefore has an important role in pharmacological lipid modification. In this paper, we examine the body of research behind ezetimibe and assess its current clinical applications in different patient subgroups.